The society’s preferred Infaq payment method: The analytic hierarchy process - Mohamad Isa Abd Jalil; Kasim Mansur; Mohd Rahimie Abd Karim; Siti Hajar Samsu; Suddin Lada; Rudy Ansar; Brahim Chekima (UK Zhende Publishing Limited, 2024)
ABSTRACT This research was conducted to examine the choice of infaq payment methods that are preferred by the community or infaq donors in Sabah. Infaq is a gift in the form of money or property spent for goodness and virtue solely to obtain the pleasure of Allah S.W.T. Infaq has several advantages that benefit all parties, including society, financial institutions, and investors. Infaq is not focused on any class, building or land, and does not require a lot of property or money. Thus, infaq has become an alternative for individuals who do not have fixed assets but have flexible assets such as cash for the purpose of donating. Therefore, everyone can do charity in the form of infaq as long as they do it voluntarily only because of the blessings of Allah S.W.T. However, public awareness and understanding of infaq is still low. Therefore, to conduct this research, a quantitative approach was used to collect data and information on infaq payment methods. This study was conducted based on the Analytic Hierarchy Process (AHP) to measure the preference of infaq donors in the choice of infaq payment method. There are several implications and limitations faced by researchers while conducting research such as time constraints in conducting surveys, obtaining cooperative respondents, and limitations of legitimate references and sources.